(untitled) (Bangladesh Journal of Infectious Diseases, 2022)
The natural spread of various harmful organisms into the environment has resulted in a wide range of diseases worldwide, including in Bangladesh. In December 2019, the world was exposed to a new virus-mediated sickness known as coronavirus disease (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which has mostly afflicted mainland China but has thereafter quickly spread to all the continents. The ongoing pandemic has taken the lives of more than 4.5 million people out of more than 10 million confirmed COVID-19 cases as of August 22, 2021. With an increase in infection and fatality rates, Dhaka, has become the most vulnerable to COVID-19. To deal with the emergency, the government of Bangladesh has imposed different measures including lockdown in various stages. The colossal effort of the government of Bangladesh deserves a standing ovation in order to mitigate the situation timely. Based on the current circumstances, it is undeniable that the situation will not be alleviated despite the government’s sincere efforts and enforcement of rules unless the country’s citizens are aware and willing to follow the prescribed prevention and control measures. This literature review compiles and summarizes the morphology, mechanism, current status, likely therapies, and preventative strategies for this novel coronavirus strain in Bangladesh. Bangladesh Journal of Infectious Diseases, April 2022;9(Suppl_1): S28-S39